Impact of Technologically Vigilant Leadership on Smart Sustainable Circular Supply Chain Management - Huy, Pham Quang; Phuc, Vu Kien (Ital Publication, 2025)
The main aim of this study is to explore how technologically vigilant leadership (TVL) impacts on smart sustainable circular supply chain management (SSCSCM) in the context of Industry 6.0. This is accomplished by analyzing the mediating effect of the digital environment management accounting system (DEMA) in the relationship between TVL and SSCSCM. This research evaluated the proposed model using two distinct statistical methods within the framework of structural equation modelling, which facilitated the assessment of both linear and non-linear correlations among the constructs. The data was obtained from a sample of respondents employed in small and medium enterprises. Linear relationships were analyzed using SmartPLS, whereas non-linear relationships were examined with WarpPLS. In both instances, the influence of TVL on SSCSCM was significant and positive, as demonstrated by CB-SEM in SmartPLS 4.1.0.9 and PLS-SEM in WarpPLS 7.0. Furthermore, DEMA partially mediated the relationship between TVL and SSCSCM. The current investigation is one of the few that provides conclusive evidence on the impact of TVL on SSCSCM. Also, it offers new insights by highlighting that DEMA partially mediates the relationship between TVL and SSCSCM. These profound insights would provide guidance for practitioners and policymakers in developing improved TVL mechanisms to leverage the advantages of DEMA and thereby strengthen SSCSCM.